Study of Anthocyanin Extraction from Red Banana (Musa sapientum L. var Rubra) Waste and Characteristics of Light Effects - Yessy Rosalina; Endang Warsiki; Anas Miftah Fauzi; Illah Sailah (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2022)
Anthocyanins are compounds responsible for plants’ blue, purple, violet, magenta, red, and orange colours. Anthocyanins are found in tropical fruits. Generally, anthocyanins are found in the peel tissues of plants. The increasing interest in anthocyanins, especially in the field of food and health, supports the development of anthocyanin exploration research. One of the uses of anthocyanins that are widely developed today is the addition of anthocyanins as indicators in smart packaging. For application on the packaging, in addition to extraction techniques, it is also necessary to assess the characteristics of anthocyanins in the environment. This study aims to examine the anthocyanin potential of red banana waste and the effect of light on anthocyanin stability. The anthocyanins observed are the result of anthocyanin extraction from the red banana peel and bracts using the maceration method. The solvent used is water acidified with citric acid. The study results showed that the total anthocyanin content in red banana bracts extract was higher than in extract from red banana peel. A concentrated extract from the bracts of a red banana contains 114.26 μg/g FW of total anthocyanins. In comparison, the concentrated extract of red banana peel contains 110.27 μg/g FW of total anthocyanins. Identification of concentrated extracts of red banana peel and flower through FTIR test, maximum wavelength test with UV-Vis and discolouration test showed that the extract contains anthocyanin compounds. Irradiation with a 25-watt bulb lamp, UV lamp and sunlight on concentrated extracts of the red banana peel and bracts showed degraded anthocyanin content. The results of this study show that the peel and flower of red bananas have the potential to be developed as a source of anthocyanins.